Development and Validation of a RP-HPLC Method for the Estimation of Amlexanox in Oral Paste Dosage Form (Dhaka University Journal of Pharmaceutical Sciences, 2012)
A simple, reproducible and efficient reversed phase high performance liquid chromatographic (RPHPLC) method has been developed for the estimation of a recently approved anti allergic drug, amlexanox in oral paste dosage form. The separations were carried out on a Zorbax Eclipse XBD, C18 column (150 x 4.6 mm; 5?m) at a flow rate of 1.50 ml/min. by using mobile phase comprising of mixed buffer (pH adjusted to 6.50) and methanol (50:50 v/v). The injection volume was 10 ?l and the peaks were detected at 244 nm. The linear dynamic range found to be in the concentration range of 15-35 ?g/ml and coefficient of correlation was found to be 0.999. The %RSD value was below 2.0 for intra-day and inter-day precision which indicated that the method was highly precise. The LOD (Limit of detection) and LOQ (Limit of quantitation) were found to be 3.8 ng/ml and 12.5 ng/ml, respectively which revealed that the method was highly sensitive. The percentage recovery of amlexanox ranged from 99.31 to 99.75%, indicating the accuracy of the method and absence of interference from the excipients present in the formulation. The proposed method was simple, fast, accurate and reproducible and hence can be applied for routine quality control operations of amlexanox in oral paste dosage form. Key words: Amlexanox, Anti allergic, RP-HPLC, LOD, LOQ. DOI: http://dx.doi.org/10.3329/dujps.v10i2.11782 Dhaka Univ. J. Pharm. Sci. 10(2): 67-70, 2011 (December)